2000
DOI: 10.3923/pjbs.2000.681.682
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Response of Wheat (Triticum aestivum L.) To Different Sowing Times and Weed Competition Durations.

Abstract: The treatments tested were two sowing dates (Mid November and end November) and six competition durations (No competition, competition for 4,6,8,10 weeks and full season competition). The experiment was laid out in a split plot arrangement with three replications placing the sowing dates and competition durations in the main and sub plots, respectively. Common weeds of wheat were allowed to compete with crop for different prescribed competition durations. The results revealed that various growth and yield comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…The evidence of this is the significant interaction between the cultivars and K fertiliser levels which has shown that Pick-row had greater biomass and lowest weed biomass at the doubled K level. This finding may partially agree with Tahir et al (2008) that increasing K fertiliser level in combination with crop cultivars increases grain yield. This study finds that splitting K fertiliser into three equal applications throughout the growing season is most likely to be useful for wheat cultivars to improve their competitive ability and grain yield.…”
Section: Resultssupporting
confidence: 89%
“…The evidence of this is the significant interaction between the cultivars and K fertiliser levels which has shown that Pick-row had greater biomass and lowest weed biomass at the doubled K level. This finding may partially agree with Tahir et al (2008) that increasing K fertiliser level in combination with crop cultivars increases grain yield. This study finds that splitting K fertiliser into three equal applications throughout the growing season is most likely to be useful for wheat cultivars to improve their competitive ability and grain yield.…”
Section: Resultssupporting
confidence: 89%
“…The results of the current study are in well agreement with those of Khan et al (2007) who reported that K application significantly increased the grain yield of wheat crop (variety Naseer) in comparison with the control. The present research work is also in agreement with those of earlier works which indicated that K application resulted in significant increases in the grain yield of two wheat crop varieties over control (Tahir et al, 2008). The findings are also supported by Qiu et al (2014) who indicated that the application of K significantly increased the grain yields of maize as compared with the control.…”
Section: Discussionsupporting
confidence: 92%